Breeding of 'DND358': A new soybean cultivar for processing soy protein isolate with a hypocholesterolemic effect similar to that of fenofibrate. (March 2022) - Song, Bo; Qiu, Zhendong; Li, Mingxue; Luo, Tingting; Wu, Qi; Krishnan, Hari B.; Wu, Junjiang; Xu, Pengfei; Zhang, Shuzhen; Liu, Shanshan
Graphical abstract: Highlights: 'DND358' is ideal raw soy material for producing hypocholesterolemic SPI powder. Modify protein subunit compositions is useful strategy for hypocholesterolemic soy breeding. DND358-SPI: a superior diet-therapy soy beverage to achieve cholesterol homeostasis. Enrich α′ subunit of 7S can be strategized in hypocholesterolemic soybean breeding. Abstract: Soy proteins have hypocholesterolemic effects (HCE). Here, we developed a soybean cultivar 'DND358', which is superior for processing hypocholesterolemic soy protein isolate beverage powder (DND358-SPI). 'DND358' carries four recessive null alleles for the α subunit of 7S globulin and the G1, G2, and G4 subunits of 11S globulin (tetra null), was selected from a population derived from a three-way cross. The tetra null mutation resulted in a compensatory increase in the α′ subunit level and arginine content. The oral administration (300 mg/kg/day) of DND358-SPI processed from 'DND358' significantly decreased the fatty liver symptoms and hepatic lipid accumulation; reduced the hepatic total cholesterol (TC), triacylglycerol (TG) levels and atherogenic index (AI) value, in rats fed a high-cholesterol diet. Conversely, DND358-SPI administration markedly elevated high-density lipoprotein cholesterol levels, to values significantly higher to those fed on fenofibrate (FF, 30 mg/kg/day), a hypocholesterolemic drug. The HCE of DND358-SPI were similar to that of FF.